Prediction of molecular mimicry between proteins from Trypanosoma sp. and human antigens associated with systemic lupus erythematosus. (November 2022) - Emiliani, Y.; Muzi, G.; Sánchez, A.; Sánchez, J.; Munera, M.
Abstract: The immune response against pathogens induces protection from future infection, however, molecular mimicry between the pathogen and the human host can promote autoreactive responses. Using in silico approaches, we identified molecular mimicry between Trypanosoma sp. and human autoantigens involved in the development of systemic lupus erythematosus (SLE). We retrieved all reported autoantigen amino acid sequences for SLE from the AAgAtlas database to perform PSI-BLAST against the Trypanosoma sp proteome to determine amino acid sequence identity with each other. The antigens given in the Protein Data Bank without a 3D structure were modeled by homology with the "Swiss Modeller Server". Epitopes shared between Trypanosoma sp. and human antigens were identified using the Ellipro server and the Immune Epitope Database (IEDB), and cross-reactive epitopes were assigned to the 3D models. 36 autoantigens involved in SLE showed molecular mimicry with Trypanosoma sp. Antigens Epitope prediction revealed that some autoantigens shared several antigenic. Highlights: Molecular mimicry could explain why some patients after being infected with Trypanosoma sp. developed Systemic Lupus Erythematous. Fifty seven antigens are shared. This suggests that infection could promote autoimmune response directed to several autoantigens in human. Some antigens have more than one shared epitope, which facilitates cross-reactivity and autoimmunity.